Electron Transfer Initiated Reactions Photoinduced by Pterins - Lorente, Carolina (2011)
Interest in the photochemistry and photophysics of pterins has increased since the participation of this family of compounds in different photobiological processes has been suggested or demonstrated in recent decades. Pterins participate in relevant biological processes, such as metabolic redox reactions, and can photoinduce the oxidation of biomolecules through both electron transfer mechanisms (Type I) and singlet oxygen production (Type II). This article describes recent findings on electron transfer-initiated reactions photoinduced by the triplet excited state of pterins and connects them in the context of photosensitized processes of biological relevance.